A CRITICAL DISCOURSE ANALYSIS OF DONALD J. TRUMP’S SPEECH ON US PRIME TIME ABOUT CORONAVIRUS IN AMERICA (International Conference on Social and Islamic Studies, 2021)
This thesis critically examines delivered speech by the American former President,Donald Trump in 2020 about coronavirus in America. The researcher has taken the datafrom YouTube that belongs to CNBC Television which was broadcasted live from theWhite House on March 11, 2020. In this speech, there is a relationship betweenlanguage, power, and ideology. Therefore Critical Discourse Analysis is conducted toreveal the concepts and hidden ideologies implied in Trump‘s speech. There are threeproblems to be solved, namely: What is the social wrong in Donald J Trump‘s speech,what are the obstacles to addressing the social wrong in Donald J Trump‘s speech, andhow the social order needs the social wrong in Donald J Trump‘s. This study usesqualitative approach and three-dimension of CDA by Norman Fairclough. The resultshows that there are three social wrongs in Donald Trump‘s speech; Trump‘s instabilityin evaluating coronavirus seriousness, Trump‘s self-positive evaluation to hisgovernment and negative evaluation to others, and COVID ―hate crimes‖ against Asianand non-originally Americans. The obstacle to social wrongs being tackles arecoronavirus outbreak in America and other countries disability to stop the virus, time ofelection campaign, and Trump misinformation in delivering his speech.